2013
DOI: 10.1161/hypertensionaha.113.01200
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Progression of Aortic Stiffness in Hemodialysis Patients

Abstract: Aortic stiffness is associated with increased cardiovascular mortality in patients with chronic kidney disease. However, the rate of progression of arterial stiffness and the role of cardiovascular risk factors in the progression of arterial stiffness has never been established in a longitudinal study. In a prospective, longitudinal, observational study, carotid-femoral pulse wave velocity and carotid-radial pulse wave velocity were assessed in 109 hemodialysis patients at baseline and after a mean follow-up o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 41 publications
4
67
0
Order By: Relevance
“…6,7,22,23 In a longitudinal study with repeated measures of PWV in hemodialysis patients, we observed that the reduction of brachial stiffness was inversely associated to baseline degree of aortic stiffness. 11 This finding along with others, 9,24 have led to propose that regression of brachial stiffness could be an adaptation to an increased central aortic stiffness. Indeed, the reduction in the stiffness of peripheral muscular arteries in the presence of high aortic stiffness will attenuate wave reflection, contributing to the shifting of the reflecting sites distally, potentially reducing the negative effect of wave reflection on central blood pressure and cardiac workload (ie, adaptation) and explaining the discordance between augmentation index and aortic stiffness.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…6,7,22,23 In a longitudinal study with repeated measures of PWV in hemodialysis patients, we observed that the reduction of brachial stiffness was inversely associated to baseline degree of aortic stiffness. 11 This finding along with others, 9,24 have led to propose that regression of brachial stiffness could be an adaptation to an increased central aortic stiffness. Indeed, the reduction in the stiffness of peripheral muscular arteries in the presence of high aortic stiffness will attenuate wave reflection, contributing to the shifting of the reflecting sites distally, potentially reducing the negative effect of wave reflection on central blood pressure and cardiac workload (ie, adaptation) and explaining the discordance between augmentation index and aortic stiffness.…”
Section: Discussionmentioning
confidence: 72%
“…11 The regression of brachial stiffness was associated to higher degree of aortic stiffness, therefore, leading to an enhanced aortic-brachial stiffness mismatch. In the context of this study, we hypothesized that aortic-brachial stiffness mismatch, as evaluated by the ratio of aortic and brachial pulse wave velocity (PWV) ratio, may prove to be a better prognostic predictor of mortality in dialysis population than aortic PWV.…”
Section: 10mentioning
confidence: 99%
See 1 more Smart Citation
“…Aortic stiffness is known to progress faster in CKD patients (31), although not all studies found this (32). Progression in APWV varies from 0.08 m/s per year in healthy normotensive persons and 0.15 m/s per year in treated hypertensive persons (31) to 0.84 m/s per year in hemodialysis patients (33). Considerable variability existed in APWV progression in our cohort, and 26.4% of patients increased by >1 m/s, a proportion of progressors similar to the study in CKD (22).…”
Section: Discussionmentioning
confidence: 99%
“…12 Immediately after BP measurements, we determined cf-PWV and carotid-radial pulse wave velocity (cr-PWV) in triplicates. 13,14 Aortic-brachial PWV ratio was calculated by the ratio of cf-PWV and cr-PWV (PWV ratio=cf-PWV/cr-PWV). For comparison, we also reported the standard cf-PWV, which was obtained taking into account differences in the transit time using the maximal upstroke algorithm and the overestimation of true distance by multiplying direct distance by 0.8.…”
Section: Hemodynamic Measurementsmentioning
confidence: 99%